Persistence and residual toxicity of some insecticides against Phenacoccus solenopsis on cotton (Gossypium spp) - DHAWAN, A K; SAINI, SARIKA; SINGH, KAMALDEEP; ANEJA, ANAND (The Indian Journal of Agricultural Sciences, 2011)
The persistence and residual toxicity of profenophos, thiodicarb, buprofezin, quinalphos, chlorantraniliprole, spirotetremate, acephate, carbaryl and chlorpyriphos at recommended concentrations in field on cotton (Gossypium spp) against first instar and adult female of mealy bug Phenacoccus solenopsis Tinsley. The mortality data for the crawlers were taken up to 24 hr, whereas for the adult females, the mortality data were recorded up to 72 hr within different exposure periods of 1, 3, 7, 10 and 14 days after application of the insecticides. Based on the index of persistence toxicity, the order of effectiveness for the crawlers of P. solenopsis were profenophos (637.1) > thiodicarb (587.9) > buprofezin (492.3) > quinalphos (407.9) > chlorantraniliprole (380.0) > spirotetramate (371.6) > acephate (345.7) > carbaryl (314.6) > chlorpyriphos (273.4). Similarly, for the adult female this order of effectiveness was profenophos (572.9) > buprofezin (483.1) > thiodicarb (430.0) > quinalphos (379.9) > chlorantraniliprole (371.6) > spirotetramate (361.3) > acephate (296.7) > carbaryl (260.0) > chlorpyriphos (252.3).,p/>